The effect of a rehabilitation program on herniated disc patients to improve some physical characteristics - بنور , أكرم; مزاري , فاتح; البشبني , فتحي (Journal of Sport Science Technology and Physical Activities, 2022)
SPSS The study aimed to know the effect of a proposed training program for therapeutic exercises for patients with herniated disc to improve some physical characteristics, as this study was conducted on (40) patients who were selected in a deliberate way using the experimental method. The axial range of motion for the right and left lumbar region and the strength of the lower back muscles before and after implementing the program for the control and experimental samples, and then comparing the results. The results showed that there were statistically significant differences in the variables under study for both groups, and the results indicated that there were statistically significant differences between the averages of dimensional measurements between the two groups and in favor of the experimental group. After three months, they were transferred to the Physiotherapy Unit, Physiotherapy Department, Ghout Al Shaal Specialized Hospital. The data was processed statistically using the SPSS statistical program